LEGAL INSTITUTION OF THE PRESCRIPTION OF CRIMINAL PROCEEDINGS BY RUSSIAN AND FOREIGN LEGISLATION - I. V. Prikhod'ko (Russian Journal of Economics and Law)
The article presents the comparative research of some items of prescriptions of institution of criminal proceedings according to Russian and foreign criminal codes. In particular, the maximal and minimal terms are analyzed; methods of their calculation and some issues of their calculation are viewed, depending on the gravity and category of the crime.